(untitled) (AYUSHDHARA, 2025)
Navratri, a biannual Hindu festival dedicated to Goddess Durga, transcends religious observance to embody a sophisticated system of seasonal adaptation. Deeply rooted in Ayurvedic principles, it aligns human physiology with nature’s rhythms during critical transitional periods known as Ritu Sandhi. Objective: To explore the ancient Ayurvedic wisdom embedded in Navratri’s fasting practices and examine their relevance and parallels to modern health trends such as intermittent fasting, metabolic health and holistic well-being. Methods: A thematic analysis of Ayurvedic texts and principles related to Agni, Ama and Dosha balance was undertaken. This was contextualized with the traditional Navratri dietary regimen and juxtaposed with modern scientific literature on fasting, gut health and metabolic regulation. Results: Seasonal Adaptation: Navratri occurs during equinoxes times of heightened physiological vulnerability mirroring Ritu Sandhi in Ayurveda, when lifestyle adjustments are crucial i.e., Fasting and Agni, Sattvic diet, modern parallels, Dosha-specific benefits. Conclusion: Navratri offers a comprehensive, time-tested health strategy rooted in Ayurvedic wisdom. Its practices foster not just physical detoxification but spiritual and emotional recalibration. In an age of fragmented wellness approaches, Navratri exemplifies a harmonious, holistic model for seasonal health, mindful living and deep ecological integration.